Optimum growth conditions of Lactobacillus brevis LIPI13-2-LAB131 in ?-galactosidase enzyme production - Aafiyah Wahyu Nur Indah -; ROHMATUSSOLIHAT ROHMATUSSOLIHAT; WINIATI PUDJI RAHAYU; FITRI SETYONINGRUM; GUNAWAN PRIADI; FIFI AFIANTI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Indah AWN, Rohmatussolihat, Rahayu WP, Setyoningrum F, Priadi G, Afianti F. 2020. Optimum growth conditions of Lactobacillus brevis LIPI13-2-LAB131 in ?-galactosidase enzyme production. Biodiversitas 21: 5403-5407. Deficiency of ?-galactosidase enzyme causes lactose to become undigested in gastrointestinal system, therefore the system needs further addition of external ?-galactosidase. The sources ?-galactosidase enzyme varies from plants, animals, and microorganisms. In industrial applications, microorganisms have become a considered potential source of ?-galactosidase. Lactobacillus brevis LIPI13-2-LAB131 had high ?-galactosidase enzyme activity, which was 7.93 U/mL. The aim of this research was to optimize the growth condition of L. brevis LIPI13-2-LAB131 in order to produce maximum ?-galactosidase enzyme activity. This research consisted of performing optimization processes using design expert 7.0 (DX7) program with response surface methodology (RSM) and partial purification of ?-galactosidase enzyme. The results of this research showed that the optimum growth conditions of L. brevis LIPI13-2-LAB131 were in 1.48% lactose level, incubation temperature of 34.91 °C, incubation time of 48.48 hours, and 2.83% inoculum size with desirability value of 0.839. The result of enzyme purification showed that value of ?-galactosidase enzyme activity increased up to 22.88 ± 0.29 U/mL with purification yield of 11.65%.